Effects of pH, Total Soluble Solids, and Pectin Concentration on Color, Texture, Vitamin C, and Sensory Quality of Mango Fruit Bar - Ngoc Duc Vu; Van Muoi Nguyen; Thanh Truc Tran (International Journal of Food Science)
Mango purée is a byproduct of the current production processes (such as freeze-drying, dehydration) after the product shaping stage or grades II and III mangoes. Currently, fruit bar is a convenient and highly nutritious snack made from fruit. The objective of this study is to utilize mango byproduct in order to develop a fruit bar processing technology, which is based on evaluating the quality (color, break force, vitamin C content, and sensory) when varying the pH of mango purée and the concentration of added pectin. Additionally, total soluble solids (TSS) after blending at 80°C were also investigated. The increase in pH, pectin concentration of mango purée, and TSS after blending showed that vitamin C content in fruit bars tended to decrease. TSS results revealed that at TSS=63°Bx, pH 3.3, and a pectin concentration of 1.3%, the product received a high rating of 6.3. Additionally, the vitamin C content of the product reached 7.82 mg/100 gDW. The results of this study are expected on the diversification of products from mango. Solving the situation that grades II and III mangoes are difficult to be commercialized and making the most of the byproduct mango flesh after certain production processes.